Vaccines for COVID-19 - state of the art - Eduardo Jorge da Fonseca Lima; Amalia Mapurunga Almeida; Renato de Ávila Kfouri
Abstract Vaccine candidates against COVID-19 have diverse compositions, from traditional inac-tivated virus vaccines to various new-generation vaccines. Currently, approximately 175 research teams worldwide are studying various vaccine possibilities as the necessityto vacci-nate the entire population against the SARS-CoV-2 virus is urgent. Although, the development of a safe and effective COVID-19 vaccine is not easy, the manufacturing, distribution, and administration of the vaccine can also face extraordinary challenges. In this review, we enhance some of the current knowledge regarding the clinical trial phases on different COVID-19 vaccine candidates, its potential strengths and disadvantages, and to discuss ethical aspects and their chances of success in large-scale applications.